BUDGET EXECUTION IN UKRAINE UNDER MILITARY AGGRESSION: CURRENT STATE AND FORECAST FOR THE FUTURE - Rusina, Yuliia O. (Journal of Strategic Economic Research, 2022)
The paper attempts to investigate modern challenges associated with budget execution in Ukraine under military aggression, as well as to identify trends of change in forecast indicators in the future. It is observed that the full-scale war of Russia against Ukraine has inflicted a heavy blow on the Ukrainian economy, thus almost ceasing the opportunity of budget execution in Ukraine which in turn spurs a significant on-going drop in budget revenues against rapidly increasing public expenditures under the pressure of military and social spending. It is reported that since the beginning of Russia’s full-scale invasion to Ukraine, the total budget deficit has increased to almost 263 billion UAH. It argued that in extremely difficult wartime, Ukrainian taxpayers who their best to fulfil their timely scheduled obligations to the budget have become a profound source of budget stuffing providing strong support for the Armed Forces. In the current realia of Russian aggression, as long as the war lasts, it is rather hard to predict medium-term prospects in the area of public finance, as well as to forecast what exactly will happen to government revenues and expenditures in the future. It is emphasized that the key development trends in government income and expenditures will fully depend on the war duration and the specifics of military actions in the future. However, the findings demonstrate that the Ukrainian economy, although slowly but gradually, is still adapting to the new wartime realia of life and doing business. Thus, the government is encouraging entrepreneurial endeavours at all levels, thereby boosting business activity. According to the results of the study, the inflation rate in Ukraine which is underpinned by the increase in fuel prices could be considered as moderate which consequently will contribute to further budget stuffing, primarily through VAT. Apart from the above, the findings suggest that in the future, Ukraine will need to critically evaluate the effectiveness of unprecedented customs duty exemptions and preferences that have started to create barriers to national producers’ competitiveness, impose additional pressure on the exchange rate, and worsen the balance of payments. However, it is argued that the current state of underpayment of customs revenues will continue. The conclusions resume that there is a critical need to expand the throughput capacity of crossing points to enhance international trade and export, in particular. In this context, the following are considered to be promising steps forward: abolishment by the European Union of all customs duties and quotas on goods and products on the Ukrainian exports during the year; announcement by the President of Ukraine of signing a bilateral agreement between Ukraine and Poland on joint border and customs control. It is noted that thanks to the adoption of the relevant legislative acts, expenditures for the national security and defense purposes and for overcoming the negative effects caused by Russia’s large-scale armed aggression against Ukraine have been increased. Within the scope of this study, the authors rely on the Law of Ukraine "On Amendments to the Law of Ukraine "On the State Budget of Ukraine for 2022" dated May 31, 2022, according to which most of the funds will be directed to national security and defense (247.8 billion UAH), assistance within the framework of the "eSupport" Program for citizens who lost their jobs due to the war (5.8 billion UAH), assistance to internally displaced persons to cover living expenses (12.5 billion UAH), payment of pensions, allowances and increases to pensions assigned under various pension programs (20 billion UAH).